Perlindungan Hukum Bagi Debitur Yang Masuk Dalam Blacklist Bank Indonesia Akibat Kelalaian Dari Leasing - Attahariq Trysnanda Putra (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
Leasing arrangements are currently limited to administration and taxes. The civil aspect, however, is still very limited in terms of agreements that regulate the rights and obligations of the parties. Therefore, parties have the freedom to determine these provisions independently. This is important because the parties encounter various possibilities in the leasing agreement, which can cause losses and cause problems. Leasing itself originates from the United States, which has a different legal system to Indonesia.